Analisis Strategi Pemasaran dan Pelayanan Pos Nextday Pada PT Pos Indonesia (Persero) Kantor Cabang Utama 40000 Kota Bandung: Digital Marketing Strategy - Ilham Harun Al Rasyid (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2024)
This research aims to analyze marketing strategies and Nextday postal services at PT Pos Indonesia (Persero) Main Branch Office 40000 Bandung City. This research uses descriptive qualitative research methods. This method is used to explore in depth various aspects of the marketing and service strategies implemented. Data was obtained through in-depth interviews, direct observation, and analysis of related documents. The research results show that PT Pos Indonesia (Persero) Main Branch Office 40000 Bandung City implements various marketing strategies including the use of effective information distribution channels, such as websites, social media and mobile applications. The next day postal service also applies delivery speed and good service quality. The conclusion of this research is that the company's effective marketing strategy continues to innovate and develop technology to speed up delivery and ensure timeliness and customer engagement, through feedback and interaction, plays an important role in the service improvement process. These findings provide insight for developing marketing strategies and improving service quality in the future.